2002
DOI: 10.1183/09031936.02.00301702
|View full text |Cite
|
Sign up to set email alerts
|

Effects of formoterol and ipratropium bromide in COPD: a 3-month placebo-controlled study

Abstract: The aim of this study was to compare the effects of formoterol, ipratropium bromide and a placebo on walking distance, lung function, symptoms and quality of life (QoL) in chronic obstructive pulmonary disease (COPD) patients.A total of 183 patients (mean age 64 yrs, 86 female) with moderate-to-severe nonreversible COPD participated in this randomised, double-blind, parallel-group study. After a 2-week placebo run-in, patients were randomised to formoterol Turbuhaler1 18 mg b.i.d. (delivered dose), ipratropium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 27 publications
2
48
0
2
Order By: Relevance
“…In this study, we have now shown that tiotropium also provides significant improvements in SWT distance compared with placebo. At study end, tiotropium increased the mean distance walked by 36 m compared with placebo, which could be considered a clinically meaningful improvement [31]. Cycle ergometry and the SWT provide different, but complementary, information.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have now shown that tiotropium also provides significant improvements in SWT distance compared with placebo. At study end, tiotropium increased the mean distance walked by 36 m compared with placebo, which could be considered a clinically meaningful improvement [31]. Cycle ergometry and the SWT provide different, but complementary, information.…”
Section: Discussionmentioning
confidence: 99%
“…A large rehabilitation study reported mean changes of 75.9 m [281]. In a large group of patients with COPD, the SWT was sensitive to the administration of formoterol and ipratopium bromide [283,284]. The endurance SWT (ESWT) seems more sensitive to change after a course of rehabilitation than the ISWT.…”
Section: Walking Testsmentioning
confidence: 99%
“…[1] The goals of COPD therapy include QOL). [2][3][4][5][6] Inhaled corticosteroids (ICSs) reduce the (i) improvements in airflow, exercise tolerance, frequency of exacerbations, [7][8][9] but have shown inhealth status and COPD symptoms (e.g. dyspnoea); consistent results in terms of reduction in mortality (ii) prevention of disease progression and exacerba-and modest effects with respect to improvement in tions; and (iii) a reduction in mortality.…”
Section: Introductionmentioning
confidence: 99%